A hybrid composite catalyst of Fe3O4 nanoparticles-based carbon for electrochemical reduction of oxygen. (24th May 2017) - Chen, Zongkun; Lin, Fei; He, Dandan; Jiang, Heqing; Zhang, Jingjing; Wang, Xin; Huang, Minghua
Abstract : We report an Fe3 O4 nanoparticles-based carbon catalyst with good electrical conductivity, abundant active sites and efficient catalytic ORR activity. Abstract : The design of efficient and cheap electrocatalysts for the oxygen reduction reaction (ORR) plays a key role for renewable energy technologies such as fuel cells and metal–air batteries. Using a simple and effective route, electronically conductive acetylene black (AB) was deliberately introduced into Fe3 O4 /HCS-600 with enough ORR active sites to be used as an ORR catalyst. The good homogenization of the electron conductor AB and the high intimate contact of Fe3 O4 /HCS-600 and AB in the composite catalyst provide the possibility of facile electron accessibility. The resulting composite catalyst exhibited a high and stable electrocatalytic activity for the ORR, which is better than Fe3 O4 /HCS-600 or AB alone. These features may offer potential for the development of efficient ORR catalysts with low cost for alkaline fuel cells.